Designing Student Internship Information System Interfaces Using the Design Thinking Method - Maulana, Jefri Achmad; Putro, Fidi Wincoko; Amri, Arni Muarifah (Journal of Information System and Informatics, 2024)
Internship programs are essential for tertiary students to gain relevant experience before entering the workforce. Managing these programs, especially in institutions such as the East Java Province Marine and Fisheries Agency (DKP), poses challenges due to the reliance on paper-based processes and the need for centralized management across 17 branches. Therefore, this research developed a "Centralized Internship Information System" (CIIS) program designed with the aim of simplifying internship registration, student placement, document management, and program monitoring at DKP and its branches. This research focuses on designing a user-friendly interface for CIIS to address these issues. The design process follows the Design Thinking method, which emphasizes deeply understanding user needs and creating innovative solutions. The effectiveness of CIIS was evaluated using the Short User Experience Questionnaire (UEQ), which assesses user experience across key aspects. The UEQ results showed an average pragmatic quality score of 1.954 (excellent) and an average hedonic quality score of 1.856, with an overall average of 1.91. These results indicate that CIIS provides a high-quality user experience, facilitating easier access to internship opportunities for students, efficient candidate selection for companies, and effective monitoring for internship managers at DKP.